IMPROVEMENT OF BEARING CAPACITY OF SHALLOW FOUNDATION ON SAND REINFORCED WITH POLYETHYLENE TEREPHTHALATE (PET) FLAKES - TAHER, NICHIRVAN RAMADHAN TAHER (Fırat Üniveristesi, 2024)
Bu çalışmada, geri dönüştürülmüş PET talaşı katkısının kumlu zeminin kayma mukavemeti özellikleri ve nihai taşıma kapasitesi üzerindeki etkisi araştırılmıştır. Kumlu zemin, farklı oranlarda (kuru ağırlıkça %0, %0,5, %0,75, %1,0 ve %1,5) PET talaşı ile güçlendirilmiştir. Düşey yükleme deneyleri laboratuvarda kum tankı içinde kare model temeller üzerinde gerçekleştirilmiştir. Testler hem katkısız kum hem de PET talaşı katkılı kum üzerinde gerçekleştirilmiştir. Tanktaki kum numuneleri PET talaşlarının her bir yüzdesi için üç farklı rölatif sıkılıkta (Dr) hazırlanmıştır (%40, %65 ve %85). Model temelin taşıma kapasitesini artırabilecek optimum donatı derinliğini belirlemek için model temelin altındaki katkılı zemin derinliğinin etkisi de araştırılmıştır. Deneysel sonuçları desteklemek için sonlu elemanlar yöntemine dayalı Plaxis 3D yazılımı kullanılarak sayısal analiz de gerçekleştirilmiştir. Deneysel çalışmalar ve sayısal analize ek olarak, literatürde iyi bilinen üç taşıma gücü teorisi ile analiz yapılmıştır. Model temellerin nihai taşıma kapasitesini hesaplamak için Terzaghi (1943), Hansen (1970) ve Vesic (1973) taşıma gücü teorileri kullanılmıştır. Deneysel sonuçlara göre, model temelin nihai taşıma kapasitesinde en iyi iyileşmeyi sağlayan optimum PET talaşı yüzdesinin %0,75 olduğu tespit edilmiştir. Kumun %0,75 PET talaşı ile iyileştirilmesinin, %40 rölatif sıkılıkta nihai taşıma kapasitesinde %84 oranında etkileyici bir artışa neden olduğu bulunmuştur. Dr = %65 rölatif sıkılıkta %64 artış gözlemlenirken, Dr = %85 rölatif sıkılıkta nihai taşıma kapasitesindeki iyileşme %56 olmuştur. Ayrıca, bu güçlendirme model temelin oturmasında Dr = %40 rölatif sıkılıkta %14,1, Dr = %65 rölatif sıkılıkta %11,3 ve Dr = %85 rölatif sıkılıkta %9,6'lık düşüşlerle kayda değer bir azalmaya yol açmıştır. Ayrıca, model temelin altında 2B derinliğinden daha fazla yapılan iyileştirme çalışmalarının sonuçlar üzerinde ihmal edilebilir bir etkisi olduğu ortaya çıkmıştır. Deneysel, teorik ve sayısal analiz sonuçları arasında karşılaştırmalar yapılmıştır. Deneysel sonuçların, %40 ve %65 rölatif sıkılıkta Vesic denkleminin sonuçlarıyla oldukça yakın sonuçlar verdiği ve %85 rölatif sıkılıkta ise Hansen denklemiyle uyumlu olduğu belirlenmiştir. Tüm sonuçların Terzaghi denkleminden önemli ölçüde saptığı görülmüştür. Sayısal analiz sonuçları, deneysel sonuçlara göre biraz daha yüksek nihai taşıma kapasitesi ve oturmalar göstermiştir, ancak sonuçların orantılı olduğu tespit edilmiştir. İlginç bir şekilde, deneysel ve sayısal sonuçlar arasındaki fark, düşük rölatif sıkılıklarda (Dr = %40 ve %65) daha belirgindir.

This study investigates the impact of adding recycled PET flakes on shear strength properties and the ultimate bearing capacity of sandy soil. The sandy soil was reinforced with different percentages of PET flakes (0, 0.5, 0.75, 1.0, and 1.5 by dry weight). Vertical load tests were conducted in a laboratory on square model footings in a soil tank. Tests were performed on both unreinforced sand and reinforced sand. The sand samples in the tank were prepared at three different relative densities (Dr): 40%, 65%, and 85% for each percentage of PET flakes. The effect of reinforcement depth beneath the model footing was also investigated to determine the optimum reinforcement depth that can improve the bearing capacity of model footing. To support the experimental results, numerical analysis was also carried out using Plaxis 3D software based on the finite element method. In addition to experimental tests and numerical analysis, three well-known bearing capacity equations from the literature were also used. The bearing capacity equations used to calculate the ultimate bearing capacity of model footings were Terzaghi (1943), Hansen (1970), and Vesic (1973). According to experimental results, it was found that the optimum percentage of PET flakes that gives the best improvement in ultimate bearing capacity load of model footing was found to be 0.75%. It was found that reinforcing sand with 0.75% PET flakes resulted in a considerable increase in the ultimate bearing capacity, at a relative density of 40%, there was an impressive 84% increase in ultimate bearing capacity. At a relative density of 65%, a substantial 64% enhancement was observed, and at a relative density of 85%, the ultimate bearing capacity improvement was 56%. Furthermore, this reinforcement led to a notable reduction in settlement of model footing, with decreases of 14.1% at a relative density of 40%, 11.3% at a relative density of 65%, and 9.6% at a relative density of 85%. It was also revealed that the reinforcement sand beyond a depth of 2B beneath the model footing has a negligible effect on the results. A comparison was made between the results of experimental, theoretical, and numerical analysis. It was found that experimental results closely matched the results of Vesic's equation at relative densities of 40% and 65%, and predominantly aligned with Hansen's equation at 85% relative density, and all results notably deviated from Terzaghi's equation. Numerical analysis results showed slightly higher ultimate bearing capacity loads and settlement than experimental results but overall there was a good agreement between them. Interestingly, the difference between experimental and numerical results was more pronounced at lower relative density (Dr = 40% and 65%) compared to higher relative density (Dr = 85%).
Polietilen tereftalat (PET) pulu kullanilarak iyileştirilmiş kuma oturan yüzeysel temelin taşima gücünün iyileştirilmesi
Keywords: İnşaat Mühendisliği